Neighborhood Social Cohesion and Walking Limitations in Ethnically Diverse Older Latinos in the United States - Vásquez, Elizabeth (Ethn Dis, 2019)
Walking is the most common form of physical activity and socially cohesive neighborhoods may provide the context for racially/ethnically diverse groups to maintain an active lifestyle, particularly at older ages. Among Latinos, the association between neighborhood cohesion and walking behaviors may additionally differ by Latino group. We examined the association between neighborhood social cohesion and walking limitations among Latinos overall and by specific Latino groups. We combined data from the 2013 to 2016 National Health Interview Survey (NHIS) and selected adults aged ≥60 years (n= 3,716). Walking limitations were assessed based on responses to the “experienced difficulty walking” survey question. Social cohesion was measured using four NHIS questions regarding neighborhood social cohesion. Logistic regression models were stratified by Latino subgroup. Mexican Americans represented the largest proportion of the sample (55%). Cubans had the highest proportion of individuals reporting high neighborhood social cohesion (51%), while Dominicans had the lowest proportion (29%). In the total sample, those with high and medium neighborhood social cohesion reported lower odds of walking limitations. Although tests for interaction were not statistically significant, stratified analyses showed that all Latino groups had lower odds of walking limitations if they lived in a high social cohesion neighborhood compared with low social cohesion neighborhoods. Our results suggest that neighborhood social cohesion is associated with walking limitations among diverse groups of older Latinos.